PENERAPAN MODEL PEMBELAJARAN PROBING PROMPTING DALAM PEMBELAJARAN MENGABSTRAKSI TEKS NEGOSIASI PADA SISWA KELAS X SMA/MA - Dian Utami (Riksa Bahasa, 2016)
Abstracts are learning to use aspects of reading and writing aspects of the curriculum is taught in 2013. Aspects read and write is a fundamental aspect which must dominated every student. In fact there are many students who are lazy to read and find it difficult to write back what they have read. Prompting probing learning model is one based learning techniques debriefing activities to guide students abstracts negotiating text. Probing prompting a model of learning that guides students actively doing activities during the learning process. The purpose of this study was to determine whether there is any significant difference between students' ability to create abstract negotiating text before and after using model prompting probing. The method used is a quasi-experimental research design one group pre-test-post-test. The sampling technique this study using purposive sampling. Data of this research is the result of pre-test-post-test capability negotiation text abstracts experimental class and the results of observation. The research shows there are differences in the negotiating text abstracting capabilities significantly between learning using learning model Probing prompting with learning that is not using that model.Keywords: learning; abstracting; the negotiating text; probing prompting.